Streptopelia senegalensis and White-breasted Kingfisher, Halcyon smyrnensis - Al- Kinany, Marwa Jamal (University of Thi-Qar Journal of Science, 2014)
The aim of the current work was to study the histological structures of glandular stomach, the proventriculus andcompare it in two types of Iraqi wild birds according to differences in diets. The birds are, Laughing dove, Streptopelia senegalensis which comprised the grainivorous bird and white breasted Kingfisher Halcyon smyrnensis which comprised the carnivorous bird. The results exhibited that the wall of the stomach (proventriculus) of two birds consists of the four layers of typical tubular organ: tunica mucosa, submucosa, muscularis and serosa. The tunica mucosa of two birds consisted of three layers, epithelium, lamina properia and muscularis , the free surface of two birds is covered with circular plicae modified from of the mucosa, The surface lining cells of this folds in both of birds is simple columnar with clear cytoplasm. The lamina propria is constituted by connective tissue with blood vessels and lymphocitary infiltration. As well as simple tubular glands. Notice that these glands are lining by simple columnar in white breasted kingfisher while simple cuboidal to columnar in laughing dove. Muscularis mucosa was a smooth muscle fibers, appears scattered along the lamina propria in laughing dove surrounds the apical part of deep proventricular glands, and extend inside the proventricular folds and entirely around the deep proventricular glands in white breasted kingfisher.Submucosa layer occupy most of the real area of the proventriculus wall containing numerous deep proventricular glands that occupy great part of submucosa. This layer is thicker in kingfisher as compared with laughing dove.